1995
DOI: 10.1093/nar/23.6.988
|View full text |Cite
|
Sign up to set email alerts
|

In vitrotranscription close to the melting point of DNA: analysis ofThermotoga maritimaRNA polymerase—promoter complexes at 75°C using chemical probes

Abstract: The interaction of DNA dependent RNA polymerase of the extreme thermophile bacteria Thermotoga maritima with a promoter bearing DNA fragment was investigated in the temperature range from 20 to 85 degrees C. We show that the T. maritima RNA polymerase recognizes and utilizes the Escherichia coli T7 A1 promoter with an efficiency similar to that of the E. coli polymerase. We have investigated the interaction of both polymerases with the same promoter over a wide range of temperatures using hydroxyl radical foot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
22
0

Year Published

1995
1995
2005
2005

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 25 publications
5
22
0
Order By: Relevance
“…5). Melting by both sigma 70 and sigma 54 holoenzymes begins near Ϫ11 and spreads downstream (7)(8)(9)(10), suggesting that sigma binding to the optimal Ϫ12͞Ϫ11 fork junction probably starts the opening process. The adjacent nontemplate strand (in the case of sigma 70) then should be bound, perhaps only when conditions allow the inhibitory Ϫ10 position gate to be unlocked.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…5). Melting by both sigma 70 and sigma 54 holoenzymes begins near Ϫ11 and spreads downstream (7)(8)(9)(10), suggesting that sigma binding to the optimal Ϫ12͞Ϫ11 fork junction probably starts the opening process. The adjacent nontemplate strand (in the case of sigma 70) then should be bound, perhaps only when conditions allow the inhibitory Ϫ10 position gate to be unlocked.…”
Section: Discussionmentioning
confidence: 99%
“…In this process, holoenzyme first binds to the promoter to form a closed complex and then opens a segment roughly from position Ϫ11 to ϩ3. Chemical modifications reveal structural distortions in closed complexes near position Ϫ11, suggesting that nucleation of promoter opening occurs near the upstream boundary of the open region (7)(8)(9)(10). The activity responsible for this critical step is not known.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This indicates that conformational changes in the DNA that accompany initiation of transcription such as promoter melting are determined by the polymerase rather than the DNA sequence (Meier et al, 1995).…”
Section: Number Of Promoter Sequence In the Figuresmentioning
confidence: 99%
“…The consensus DNA sequence of the Ϫ10 region is 5Ј-TATAAT-3Ј in the nontemplate strand, with the first T being at the Ϫ12 position (1). To elucidate the molecular procedures of base unpairing during open complex formation, altered forms of DNA (depurinated, nicked, forked, or with single-stranded gap) in the Ϫ10 region were used as templates (10,(14)(15)(16)(17)(18)(19). These studies suggested that base unpairing involves an initial distortion or localized melting event around Ϫ11 (16,20).…”
Section: U Nder Ordinary Physiological Conditions Transcription Inmentioning
confidence: 99%